AAV-mediated PEX1 gene augmentation improves visual function in the PEX1-Gly844Asp mouse model for mild Zellweger spectrum disorder - Catherine Argyriou; Anna Polosa; Ji Yun Song; Samy Omri; Bradford Steele; Bruno Cécyre; Devin S. McDougald; Erminia Di Pietro; Jean-François Bouchard; Jean Bennett; Joseph G. Hacia; Pierre Lachapelle; et al. (Molecular Therapy: Methods & Clinical Development, 2021)
Patients with Zellweger spectrum disorder (ZSD) commonly present with vision loss due to mutations in PEX genes required for peroxisome assembly and function. Here, we evaluate PEX1 retinal gene augmentation therapy in a mouse model of mild ZSD bearing the murine equivalent (PEX1-p[Gly844Asp]) of the most common human mutation. Experimental adeno-associated virus 8.cytomegalovirus.human PEX1.hemagglutinin (AAV8.CMV.HsPEX1.HA) and control AAV8.CMV.EGFP vectors were administered by subretinal injection in contralateral eyes of early (5-week-old)- or later (9-week-old)-stage retinopathy cohorts. HsPEX1.HA protein was expressed in the retina with no gross histologic side effects. Peroxisomal metabolic functions, assessed by retinal C26:0 lysophosphatidylcholine (lyso-PC) levels, were partially normalized after therapeutic vector treatment. Full-field flash electroretinogram (ffERG) analyses at 8 weeks post-injection showed a 2-fold improved retinal response in the therapeutic relative to control vector-injected eyes. ffERG improved by 1.6- to 2.5-fold in the therapeutic vector-injected eyes when each cohort reached 25 weeks of age. At 32 weeks of age, the average ffERG response was double in the therapeutic relative to control vector-injected eyes in both cohorts. Optomotor reflex analyses trended toward improvement. These proof-of-concept studies represent the first application of gene augmentation therapy to treat peroxisome biogenesis disorders and support the potential for retinal gene delivery to improve vision in these patients.